Cu(II) conjugation along the transformation of a vitamin K-3 derivative to a dinaphthoquinone methide radical - Badave, Kirti D.; Patil, Shalaka S.; Khan, Ayesha A.; Srinivas, Darbha; Butcher, Raymond J.; Gonnade, Rajesh G.; Puranik, Vedavati G.; Pinjari, Rahul V.; Gejji, Shridhar P.; Rane, Sandhya Y. (New Journal of Chemistry, 2014)
1,1'-Methide-bi-vitamin K-3 (B) has been isolated as a dinaphthoquinone methide radical (DNQM) by the transformation of 1-imino(acetylhydrazino)-vitamin K-3 (A). The transformation follows a biomimetic activation pathway mediated via Cu(II) ion catalyzed oxidative coupling. Single crystal X-ray and electron spin resonance (ESR) experiments combined with density functional calculations elucidate the ``resonance structure'' of the DNQM radical (B). Fluorescence investigations reveal that DNQM facilitates interaction with the cysteine residue. As compared to the parent substrate, B shows a depletion in the level of GSH, triggering apoptosis in HeLa cells.